2018
DOI: 10.1074/jbc.ra117.001611
|View full text |Cite|
|
Sign up to set email alerts
|

CRISPR RNA and anti-CRISPR protein binding to the Xanthomonas albilineans Csy1-Csy2 heterodimer in the type I-F CRISPR-Cas system

Abstract: Clustered regularly interspaced short palindromic repeats (CRISPRs) and CRISPRassociated (Cas) proteins provide microbial adaptive immunity against bacteriophages. In type I-F CRISPR-Cas systems, multiple Cas proteins (Csy1-4) comprise a surveillance complex (Csy complex) with CRISPR RNA (crRNA) for target recognition. Here, we report the biochemical characterization of the Csy1-Csy2 subcomplex from Xanthomonas albilineans, including the analysis of its interaction with crRNA and also AcrF2, an anti-CRISPR (Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 60 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…Evolutionary classification of this CRISPR/ cas system indicated that it belongs to class 1, type I-F, initially identified in Yersinia pseudotuberculosis [ 57 ]. The same type of CRISPR/cas system has been reported very recently in Xanthomonas albilineans [ 58 ].…”
Section: Resultsmentioning
confidence: 58%
“…Evolutionary classification of this CRISPR/ cas system indicated that it belongs to class 1, type I-F, initially identified in Yersinia pseudotuberculosis [ 57 ]. The same type of CRISPR/cas system has been reported very recently in Xanthomonas albilineans [ 58 ].…”
Section: Resultsmentioning
confidence: 58%
“…Using individually purified recombinant proteins, we asked whether AcrIF7 interacts with the X. albilineans Cas8f–Cas5f heterodimer. We previously showed that X. albilineans Cas8f and Cas5f proteins stably form a heterodimeric complex that is capable of binding the 5′ crRNA handle ( 24 ). AcrIF2, a previously characterized type I-F Acr protein, associates tightly with the X. albilineans Cas8f–Cas5f heterodimer with an equilibrium dissociation constant ( K D ) of 7.2 nM ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that X. albilineans Cas8f and Cas5f proteins stably form a heterodimeric complex that is capable of binding the 5′ crRNA handle ( 24 ). AcrIF2, a previously characterized type I-F Acr protein, associates tightly with the X. albilineans Cas8f–Cas5f heterodimer with an equilibrium dissociation constant ( K D ) of 7.2 nM ( 24 ). AcrIF2 also shows similar affinity for the complete P. aeruginosa Csy complex ( 10 , 11 ).…”
Section: Resultsmentioning
confidence: 99%
“…All Acrs characterized to date function by inhibiting either the CRISPR surveillance complexes or the effector nucleases ( Bondy-Denomy et al., 2015 , Pawluk et al., 2016b , Pawluk et al., 2017 , Wang et al., 2016a , Wang et al., 2016b , Chowdhury et al., 2017 , Dong et al., 2017 , Guo et al., 2017 , Harrington et al., 2017 , Hynes et al., 2017 , Peng et al., 2017 , Rauch et al., 2017 , Shin et al., 2017 , Yang and Patel, 2017 , Hong et al., 2018 ). These acr genes were first identified in temperate Pseudomonas phages ( Bondy-Denomy et al., 2013 ) and can rescue phage from CRISPR-mediated extinction ( van Houte et al., 2016b ).…”
Section: Introductionmentioning
confidence: 99%